Pengaruh Kepemimpinan, Keadilan, dan Kepercayaan pada Keterlibatan Kinerja Dosen - Yuyun Elizabeth Patras; Rais Hidayat (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2019)
Work immersion, for lecturers, is a crucial element to the development of a university. Efforts to foster their contributions have to be continuously improved. This research aims to investigate the best way to advance lecturer’s work participation by examining causal relationship between lecturer’s work involvement with leadership variables, organizational justice and organizational trust. This research employs quantitative approach using path analysis, and was conducted in three private universities in Bogor. Total population of this research is 707 lecturers, whereas the sample taken was 130 people. The research found that: (1) there is a significant direct positive impact of leadership toward lecturer’s work involvement; (2) there is a significant positive impact of organizational justice toward lecturer’s work participation; and (3) there is a significant direct impact between trust toward organization and lecturer’s work contribution. Based on that findings, effective leadership, justice, and trust to the organization would improve lecturer’s work involvement in private university.